Gender and ICTs in Development - Wambui, Mercy (Technical Centre for Agricultural and Rural Cooperation, 2002)
Picture this. Anastacia Namusonge is over 70 years old, a grandmother and a farmer in Uganda. She has had no formal education but can confidently turn the ´pages´ of a CD-ROM on setting up small-scale businesses.